Vacuum-enhanced anaerobic fermentation: Achieving process intensification, thickening and improved hydrolysis and VFA yields in a single treatment step. (15th July 2022) - Haroun, Basem; Bahreini, Gholamreza; Zaman, Masuduz; Jang, Eunkyung; Okoye, Frances; Elbeshbishy, Elsayed; Santoro, Domenico; Walton, John; Al-Omari, Ahmed; Muller, Chris; Bell, Kati; Nakhla, George
Highlights: IntensiCarb TM (IC) is a novel technology that allows simultaneous thickening and fermentation in a single treatment step. IC improved both VFA and hydrolysis yields compared to control fermenter. IC produced condensate at higher quality with no solids and low nutrient contents. Applying vacuum to the fermenter leads to doubling the volumetric organic loading. Applying vacuum has no negative impact on fermentative bacteria and methanogens. Abstract: This study assessed the feasibility of a novel vacuum-enhanced anaerobic digestion technology, referred to as IntensiCarb TM (IC), under mild vacuum pressure (110 mbar), compared to a control (conventional fermenter), and evaluated the impact of the vacuum on the activities of various microbial groups. Both fermenters (test and control) were operated with mixed (50% v/v) municipal sludge at solids concentrations of 2–2.5%, pH of 7.8–8.1, 40–45 °C, a theoretical solids retention time (SRT) of 3 days with different hydraulic retention times (HRT). The intensification factor (IF) of the IC, defined as SRT/HRT, was controlled at 1.3 and 2.0. Simultaneous thickening and fermentation intensification were achieved. Compared with the control, the IC, despite the shorter HRTs, achieved 29.5 to 90.2% increase in the VFA yield (79 to 116 mg ΔVFA/ g VSS vs 61 mg ΔVFA/ g VSS), and 16.2% to 56.4% increase (280 to 377 mg ΔsCOD/ g VSS vs 241 mg ΔsCOD/ g VSS), in the hydrolysis yield. Fermentate from the IC exhibited comparable specific denitrification rates to acetate. Further, the solids-free condensate contained low nutrient concentrations, and thus was far superior to a typical centrates from dewatering as a carbon source. No adverse effects of vacuum on the activity of fermentative bacteria and methanogens were observed. This study demonstrated that the IC can be deployed as an intensification technology for both fermentation and anaerobic digestion of biosolids with the additional significant advantage, i.e. elimination of sidestream ammonia treatment requirements. Graphical abstract: Image, graphical abstract